Electrochemical Performance of Modified Graphite Anode Materials for Lithium-Ion Batteries - Eko Prasetya; William Abednego Pardede; Abdulloh Rifai; Muhammad Darma Raditya; Fawaidzdurahman Fawaidzdurahman; Yudi Hidayat (Department of Mechanical and Industrial Engineering, 2026)
This study investigates the pilot-scale synthesis and characterization of chemically modified graphite anodes for lithium-ion batteries (LIBs), using potassium hydroxide (KOH) etching to enhance surface properties and lithium storage capacity. The low-cost, scalable modification process led to increased interlayer spacing, as confirmed by X-ray diffraction (XRD), indicating successful structural transformation. Scanning electron microscopy (SEM) analysis revealed significant morphological changes with increased porosity, while Brunauer–Emmett–Teller (BET) surface analysis showed a substantial rise in specific surface area, from 10 m²/g to 80 m²/g, confirming the formation of porous structures. Thermogravimetric and Fourier-transform infrared spectroscopy (FTIR) analyses demonstrated high thermal stability and minimal surface functionalization, respectively. Electrochemical performance was evaluated using 18650 cylindrical cells with LiFePO₄ (LFP) cathodes. Batch 4 and 5 cells exhibited optimal N/P ratios of 1.2–1.3, achieving improved specific capacity and cycle stability. Among all batches, Batch 6 demonstrated the highest capacity retention and coulombic efficiency during rate performance testing. These results highlight the potential of KOH-modified graphite as a high-performance anode material and offer valuable insights into scalable production strategies for next-generation LIBs.